Tissue Engineering in Regenerative Medicine - Bernstein, Harold S.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2011)
Over the past decade, significant advances in the fields of stem cell biology, bioengineering, and animal models have converged on the discipline of regenerative medicine. This volume provides a state-of-the-art report on tissue engineering toward the goals of tissue and organ restoration and regeneration. Examples from different organ systems are used to illustrate progress with growth factors to assist in tissue remodeling; the capacity of stem cells for restoring damaged tissues; novel synthetic biomaterials to facilitate cell therapy; transplantable tissue patches that preserve three-dimensional structure; synthetic organs generated in culture; aspects of the immune response to transplanted cells and materials; and the development of suitable animal models for non-human clinical trials. Throughout the chapters, the reader will observe a common theme of basic discovery informing clinical translation, and clinical studies in animals and humans guiding subsequent experiments at the bench.
Hematopoietic Stem Cell Transplantation: Reflections on Yesterday and Thoughts for Tomorrow -- Human Embryonic Stem Cells in Regenerative Medicine -- Current Status of Induced Pluripotent Stem Cells -- Mesenchymal Stromal Cells: Latest Advances -- The Role of Mechanical Force in Guiding Tissue Differentiation -- Synthetic Multi-Level Matrices for Bone Regeneration -- Directing Cell Fate Through Biomaterial Microenvironments -- Basic Considerations with Cell Sheets -- Myocardial Repair and Restoration -- Skeletal Muscle Engineering: The Need for a Suitable Niche -- Restoring Blood Vessels -- Engineering Functional Bone Grafts -- Engineering Functional Cartilage Grafts -- Adult Stem Cells and Regeneration of Adipose Tissue -- Hollow Organ Engineering -- Engineering Complex Synthetic Organs -- Liver Regeneration and Tissue Engineering -- Immune Modulation for Stem Cell Therapy -- Regenerative Medicine and the Foreign Body Response -- Small Animal Models of Tissue Regeneration -- Use of Large Animal and Nonhuman Primate Models for Cell Therapy and Tissue Engineering.
Keywords: Life sciences; Biotechnology; Cytology; Stem cells; Life Sciences; Stem Cells; Cell Biology; Biotechnology